An Analysis of Early Age Marriage in The Economic Resilience of The Family at Kelurahan Jua-Jua Kecamatan Kayu Agung - Zubaidah Zubaidah; Evy Ratna Kartika Waty (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
Marriage is generally carried out by adults or already in ideal conditions for marriage, but until now there is still the practice of early marriage that occurs in Jua-Jua Village, Kayuagung District. This study aims to look at the analysis of early marriage in the economic resilience of families in Jua-Jua Village, Kayu Agung District by using a quantitative method approach, data collection techniques using questionnaires and interviews. Respondents in this study were 32 women who married early and one parent whose child married early was carried out by interview. The data analysis technique used is to find the percentage of the respondent's achievement level (TCR). The results showed that the TCR calculation on the indicator of family residence with a value of 80.86 is categorized as good. On the family income indicator with the TCR calculation, the value of 56.72 is categorized as poor, the indicator for children's educational needs with a value of 48.04 is categorized as not good and the indicator for family financial security with a TCR calculation value of 48.63 is categorized as not good. Through the calculation of the respondent's level of achievement, the average value of family economic resilience in early married couples is 58.56. This figure illustrates that the economic resilience of families in early married couples in Jua-Jua Village, Kayu Agung District is not good. Keywords: Early marriage, family economic resilience.